Higher order risk attitudes, demographics, and financial decisions - Noussair, Charles; Trautmann, Stefan T.; Kuilen, Gijs van de (Discussion paper, 2011)
We conduct an experiment to study the prevalence of the higher order risk attitudes of prudence and temperance, in a large demographically representative sample, as well as in a sample of undergraduate students. Participants make pairwise choices between lotteries of the form proposed by Eeckhoudt and Schlesinger (2006). The choices in these lotteries isolate prudent from imprudent, and temperate from intemperate, behavior. We relate individuals’ risk aversion, prudence, and temperance levels to demographics and financial decisions. We observe that the majority of individuals’ decisions are consistent with risk aversion, prudence, and temperance, in both the student and the demographically representative sample. An individual’s level of prudence is predictive of his wealth, saving, and borrowing behavior outside of the experiment, while temperance predicts the riskiness of portfolio choices. Our findings suggest that the coefficient of relative prudence for a representative individual is approximately equal to two.